Penerapan Akad Wadah pada Bank BTN Syariah: Penerapan Akad Wadah pada Bank BTN Syariah - Sari, Dinna Intika; Bakhri, Saiful (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2024)
The implementation of the Wadiah contract in the sharia banking industry, especially at Bank BTN Syariah, is an effort to provide security to customers in saving and managing funds in accordance with sharia principles. The aim of this research is to determine the application of the wadiah contract to savings products at BTN Syariah bank. The method used is qualitative, by analyzing data obtained through interviews with bank staff and customers who use wadiah contracts. The conclusion of this research is that the implementation of the wadiah contract by Bank BTN Syariah is the main basis for maintaining customer trust and strengthening the bank's position in the sharia banking industry. In facing the challenges and dynamics that continue to develop, Bank BTN Syariah needs to continue to improve its ability to consistently apply this principle while continuing to provide services that are competitive and in accordance with Islamic law.Keywords: Bank BTN Syariah, wadiah contract, sharia principles, fund security, transparency, customer trust.